2014
DOI: 10.1016/j.jallcom.2014.05.121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of segregations formed in unmodified and Sr-modified Al–Si alloys studied by atom probe tomography and transmission electron microscopy

Abstract: Comparison of segregations formed in unmodified and Sr-modified Al-Si alloys studied by atom probe tomography and transmission electron microscopy, 2014, Journal of Alloys and Compounds, (611) AbstractThe mechanical properties of Al-7 wt.% Si can be enhanced by structural modifications of its eutectic phase. Addition of low concentrations of certain elements, in this case 150 wt-ppm Sr, is enough to cause a transition from a coarse plate-like Si structure to a finer coralline one. To fully understand the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 49 publications
6
26
0
Order By: Relevance
“…Ahead of the growing Si crystal a diffusion profile is formed by segregation leading to constitutional undercooling. The solubilities of Al and Sr in Si are ~400 at-ppm and ~40 at-ppm, respectively [16], which is less than the expected concentration in the liquid. Therefore, both these elements are expected to be enriched ahead of the solidification front.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Ahead of the growing Si crystal a diffusion profile is formed by segregation leading to constitutional undercooling. The solubilities of Al and Sr in Si are ~400 at-ppm and ~40 at-ppm, respectively [16], which is less than the expected concentration in the liquid. Therefore, both these elements are expected to be enriched ahead of the solidification front.…”
mentioning
confidence: 69%
“…Recent investigations have revealed that Al forms segregations with Sr or Na in the Si eutectic phase [16][17][18]. The presence of Al in combination with the modifier was not considered in previous theories when explaining the origin of the modification [5,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of these three elements to cosegregate was regarded as indicative that these promote formation of new twins. Barrirero et al 10 similarly identified rod-like nanoscale cosegregations (responsible for smoothening of Al-Si boundaries in eutectic phase) and particle-like and planar cosegregations (favoring formation of twin boundaries). The particle-like segregations were also observed in the unmodified alloy, though obviously containing exclusively Al.…”
Section: Discussionmentioning
confidence: 97%
“…Atom probe tomography (APT) has been used by several researchers to look into the segregation of the modifying element within Al-Si alloys. [7][8][9][10][11][12] Past studies have explored the application of Y as a modifier of Al-Si alloys. Researchers used varying amounts of Y, between 200 ppm and 6000 ppm, and observed that, in presence of Y, the Si eutectic forms a refined plate-like morphology rather than a fibrous one.…”
Section: Introductionmentioning
confidence: 99%